Traditional fermented foods with anti-aging effect: A concentric review. (August 2020) - Das, Gitishree; Paramithiotis, Spiros; Sundaram Sivamaruthi, Bhagavathi; Wijaya, Christofora Hanny; Suharta, Sigit; Sanlier, Nevin; Shin, Han-Seung; Patra, Jayanta Kumar
Graphical abstract: Highlights: Consumption of fermented foods is associated with health benefits. Research has focused on effective strategies to delay aging & increase lifespan, well-being. Fermented food products are promising alternative due to immunomodulatory effect. A series of anti-aging related benefits have been reported from fermented foods. For example, specific compounds such as genistein and daidzein in fermented soybeans. Abstract: Fermentation has been applied since antiquity as a way to preserve foodstuff or as a necessary step in the production of a variety of products. The research was initially focused on accurate description of production procedure and identification of parameters that may affect the composition and dynamics of the developing micro-communities, since the major aim was standardization and commercial exploitation of the products. Soon it was realized that consumption of these products was associated with an array of health benefits, such as anti-hypertensive, anti-inflammatory, anti-diabetic, anti-carcinogenic and anti-allergenic activities. These were credited to the microorganisms present in the fermented products as well as their metabolic activities and the bio-transformations that took place during the fermentation process. Aging has been defined as a gradual decline in the physiological function and concomitantly homeostasis, which is experienced by all living beings over time, leading inevitably to age-associated injuries, diseases, and finally death. Research has focused on effective strategies to delay this process and thus increase both lifespan and well-being. Fermented food products seem to be a promising alternative due to the immunomodulatory effect of microorganisms and elevated amounts of bioactive compounds. Indeed, a series of anti-aging related benefits have been reported, some of which have been attributed to specific compounds such as genistein and daidzein in soybeans, while others are yet to be discovered. The present article aims to collect and critically discuss all available literature regarding the anti-aging properties of fermented food products.